Pengaruh Country of origin, Perceived quality, dan Brand image terhadap Puchase Decisions Smartphone Iphone dengan Customer trust Sebagai Variabel Mediasi - Irani Agustina; Any Eliza; Nurhayati Nurhayati (Jurnal Bisnis Kreatif dan Inovatif, 2024)
The development of increasingly advanced technology has a major influence on the world of the communications industry and has led to competition between smartphone manufacturers. They compete to produce advantages in products that will be marketed. The number of iPhone users among students has become commonplace, when they buy a product, of course, they do not only see the advantages offered, but they also see the brand they will buy and country of origin, perceived quality and brand image are factors that cannot be underestimated in influencing purchase decisions through customer trust. This research uses quantitative methods with a sample size of 100 respondents. Data sources are primary data and secondary data, primary data obtained from the distribution of questionnaires. This study uses probability sampling with random sampling technique. For the data analysis process using the Smart-PLS version 4.1.0.3 processing tool. Based on the results of research on direct effects, it shows that perceived quality and brand image do not have a significant effect on purchase decisions, while country of origin has a significant effect. The indirect effect shows that customer trust does not mediate the relationship from the influence of country of origin and brand image on purchase decisions, but customer trust is able to mediate the relationship from the influence of perceived quality on purchase decisions.